WAYS OF FORMING THE SPEECH CULTURE OF YOUNGER SCHOOLCHILDREN - Есназар , Асель; Кошербаева, Азиза; Кошкарова, Мадина; Уайдуллакызы, Эльмира (Pedagogy and Psychology, 2022)
The article defines the ways of forming the speech culture of younger schoolchildren. The problem of speech culture formation is determined by the properties and function of language, its social role and the nature of its use. In the formation of the speech culture of younger schoolchildren, the forms of working with a word, working with a phrase and a sentence, teaching coherent speech were shown. Exercises were grouped to determine the meaning and features of the word. The knowledge, skills, and skills necessary for the formation of speech culture are determined. Taking into account the urgency of the problem of the formation of the speech culture of younger schoolchildren as a whole, a system of special exercises has been developed. Research work was also carried out to determine the ways of forming the speech culture of younger schoolchildren, as a result of which students learned to make sufficiently consistent sentences, accurately convey a thought in accordance with a logical sequence, use words, phrases, adequately and clearly answer a question. Based on the results of the study, it was found that the exercises developed by us play a huge role in the formation of the speech culture of younger schoolchildren.